KEEFEKTIFAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN LITERASI NUMERASI DASAR SISWA KELAS V SD - Dyah Indraswati; Ketut Sri Kusuma Wardani (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2022)
The quality of learning related to mathematics, science, and literacy, especially for elementary school students is still far behind, not leats at SDN Tanak Embang. This study aims to determine the effectiveness of the Think Talk Write (TTW) learning model on the basic numeracy literacy skills of fifth-graders at SDN Tanak Embang. This quantitative research uses a quasi-experimental method. The population in this study were all fifth-grade students at SDN Tanak Embang. A simple random sampling technique was used to determine the control and the experimental classes. Class VA with 21 students as the control class and class VB with 21 students as the experimental class. The research design used was a pretest-posttest control group design. The instrument used in this study was 10 questions about the description of simple flat shapes. The analysis prerequisite test used a normality test and homogeneity test. The N-gain test was used to see the difference between the pretest and posttest scores in the control classes and the experimental class. The Wilcoxon test showed that  difference between the pretest and posttest scores, where the posttest scores were higher than the pretests. The N-Gain test shows that the use of the TTW learning model is less effective in the basic numeracy literacy abilities of fifth-grade elementary school students. In contrast, the use of conventional learning models is not effective in the basic numeracy literacy skills of fifth-grade elementary school students.